Competing Risks in a Time on the Market Analysis - Erik R. de Wit (Tinbergen Institute, 2010)
Theoretical models on the selling process in the housing market are scarce. Taylor (1999) specifies a model where time-on-the-market gives a quality signal of the house to potential buyers if inspection outcomes of the house are not public. We specify a duration model with competing risks, where the competing risks are a sale or a withdrawal from the market. We use a unique administrative dataset from the Netherlands. We find negative duration dependence in the hazard of sale and positive duration dependence in the hazard of withdrawal confirming the empirical predictions from Taylor (1999).
Keywords: G12; C41; D14; R30; 330; time-on-the-market; duration models; household finance; housing market; Wohnungsmarkt; Produktqualität; Konsumentenverhalten; Lernprozess; Niederlande